A Network Analysis of the Intersectoral Linkages Between Manufacturing and Other Industries in China and Italy. (January 2019) - Monarca, Umberto; Cassetta, Ernesto; Re, Michele Lo; Meleo, Linda
In recent years, the structural changes in global manufacturing and the economic crisis have sparked renewed interest in the role of manufacturing sector in driving economic development. Based on data from the World Input–Output Database (WIOD), this article uses network analysis (NA) to describe and compare inter-sectoral linkages between manufacturing and other sectors in two national economies, Italy and China, characterized by different stages of industrialization. The main metrics of the networks identified (at both node and network level) are discussed from an economic perspective. Besides confirming that manufacturing still has a fundamental role as the main source of demand for other economic activities in both countries, results highlight some fundamental differences in the structural characteristics of inter-sectoral linkages between China and Italy. Our exploratory analysis provides policymakers a complementary framework to illustrate backward and forward linkage effects, as well as potential knowledge and technology flows between industries.